Transcriptomic analysis reveals pathophysiological relationship between chronic obstructive pulmonary disease (COPD) and periodontitis - Shuqin Liu; Yun Fu; Dirk Ziebolz; Simin Li; Gerhard Schmalz; Fan Li (BMC, 2022)
Abstract Background The aim of this study was to detect potential crosstalk genes, pathways and immune cells between periodontitis and chronic obstructive pulmonary disease (COPD). Methods Chronic periodontitis (CP, GSE156993) and COPD (GSE42057, GSE94916) datasets were downloaded. Differential expressed genes (DEGs; p < 0.05) were assessed and screened for overlapping results, following functional pathway enrichment analyses (p < 0.05). The xCell method was used to assess immune cell infiltration relationship between CP and COPD. Features of the detected cross-talk genes were revealed using conventional Recursive Feature Elimination (RFE) algorithm in R project. Receiver-operating characteristic curves were applied to evaluate the predictive value of the genes. Furthermore, Pearson correlation analysis was performed on crosstalk markers and infiltrating immune cells in CP and COPD, respectively. Results A total of 904 DEGs of COPD and 763 DEGs of CP were acquired, showing 22 overlapping DEGs between the two diseases. Thereby 825 nodes and 923 edges were found in the related protein-protein-interaction network. Eight immune cell pairs were found to be highly correlated to both CP and COPD (|correlation coefficients |> 0.5 and p-value < 0.05). Most immune cells were differently expressed between COPD and CP. RFE identified three crosstalk genes, i.e. EPB41L4A-AS1, INSR and R3HDM1. In correlation analysis, INSR was positively correlated with Hepatocytes in CP (r = 0.6714, p = 0.01679) and COPD (r = 0.5209, p < 0.001). R3HDM was positively correlated with Th1 cells in CP (r = 0.6783, p = 0.0153) and COPD (r = 0.4120, p < 0.01). Conclusion EPB41L4A-AS1, INSR and R3HDM1 are potential crosstalk genes between COPD and periodontitis. R3HDM was positively correlated with Th1 cells in both diseases, while INSR was positively correlated with Hepatocytes in periodontitis and COPD, supporting a potential pathophysiological relationship between periodontitis and COPD.